Integration of Location Quotient, Shift Share, and Klassen Typology for Leading Sector Identification and Regional Economic Strategy in Bengkulu - Ledia Sesita; Ketut Sukiyono; Bambang Agoes Hermanto (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This study aims to identify leading sectors and formulate development strategies for Bengkulu Province, with a focus on Bengkulu City and Rejang Lebong Regency. The research addresses the need for more targeted regional economic policies based on sectoral potential. Methodology: The study employs constant-price Gross Regional Domestic Product (GRDP) data from 2020 to 2024. Analytical methods include Location Quotient (LQ), Shift Share Analysis, Klassen Typology, and SWOT Analysis. Results: The results indicate that Bengkulu City is dominated by the tertiary sector, particularly trade, transportation, information and communication, business services, education, and health, which serve as the base sectors. Rejang Lebong Regency remains dependent on agriculture but has begun to diversify through the growth of services and trade. Findings: Klassen Typology classifies Rejang Lebong as a fast-growing and advanced region, while Bengkulu City functions as a regional service hub. The integration of LQ, Shift Share, and Klassen Typology identifies agriculture, tourism, trade, and modern services as priority sectors. SWOT analysis suggests strengthening urban services and tourism in Bengkulu City and increasing agricultural value-added through agrotourism and agro-processing in Rejang Lebong Regency. Novelty & Originality: The novelty of this study lies in integrating quantitative regional analysis with SWOT to develop a regional value chain–based strategy, positioning Bengkulu City as a service and distribution center and Rejang Lebong as a production area. Conclusions: These findings provide empirical support for more focused and sustainable regional development policies. Type of Paper: This paper is an empirical research paper.